PENGENALAN BUDAYA JEPANG DAN PENINGKATAN KEMAMPUAN PEMBUATAN POSTER SISWA SMKN 11 MALANG - Lailatul Husna; Rike Febriyanti; Syarifuddin Rohman (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
The community service carried out by Pengabdian kepada Masyarakat team at SMKN 11 Malang aims to introduce Japanese culture and language by making posters to increase understanding of Japanese culture and the potential for labor or further study in Japan. Community Service was carried out with two training materials and organized a poster-making competition with materials in the form of Japanese culture and poster-making techniques. The training was conducted on 20 and 22 July 2022. The poster-making competition was held from 22 July to 1 August 2022 in groups. This research also produces art content products, namely posters with elements of Japanese culture. The result of this training and poster-making competition is that the students of SMKN 11 Malang are able to make promotional posters for the Japanese Language Education Study Program well. Students of SMKN 11 Malang majoring in Multimedia and Nursing and collaborating to make promotional posters well in groups.